ADMINISTRATIVE INCOMING LETTER AND OUTGOING LETTER HOSPITALS USING MEKAR SARI BEKASI MICROSOFT VISUAL BASIC 6.0 - Siti Juleha; Jalinas Jalinas, Skom (Jurnal Sistem Informasi, 2002)
Problems letters - correspondence is one thing that could be considered quiteimportant because the letter is a necessary information for individuals and companies.Because the handling of letters - correspondence must be good and tidy order ifneeded can be found quickly.